PENGARUH TERPAAN IKLAN NU GREEN TEA VERSI NCT 127 DI INSTAGRAM TERHADAP MINAT BELI ( Survey Kepada Followers Akun Instagram Nu Green Tea ) - Eko Hardiyanto (2021)
This study is entitled "The Influence of Nu Green Tea Advertisements on NCT 127 Version on Instagram on Buying Interest (Survey for Nu Green Tea Instagram Account Followers)". The purpose of this study is to find out how much influence NU Green Tea Version NCT 127 on Instagram has on buying interest. The results of this study through various tests such as correlation test, coefficient of determination test and hypothesis testing with T test. The correlation test uses the Pearson product moment correlation test with a result of 0.850, which indicates that the correlation is perfect between the two variables. The coefficient of determination test has a result of 70.5% which indicates that the X variable has a positive influence (Instagram advertising) on the Y variable (buying interest). The hypothesis test has a t-count value of 15.997, while the t-table value is 1.661 and the significance value is 0.10. Based on this value, Ho is rejected and Ha is accepted, and it can be concluded that the NCT 127 Version of Nu Green Tea Advertisement on Instagram has an effect on buying interest.